Viewboard Effectiveness on Raharja Internet Cafe Website as Sales Information Submission Media - Nurhaeni, Tuti; Karts, Kawl W; Hardini, Marviola (Pandawan, 2019)
Information is a key to success in communicating. Communication will not be possible without information. But if the information we convey is wrong it will cause a problem. At Raharja University there is a facility that provides needs services to students such as searching for material, printing, scans, and binding documents, there are also accessories and service places if there are students who have problems with the equipment given for study, Raharja Internet Cafe. Raharja Internet Cafe has a website to be used by students who want to order their needs. However, the admin who maintains Raharja Internet Cafe cannot monitor what products or goods are the best-selling or the most sold because they are not well monitored. With no monitoring of the admin sales process or the guard cannot report the goods to the University, or the conventional data recording process. These problems are certainly considered ineffective because Raharja University is engaged in technology in each of its lecture activities. Creating a viewboard on the Raharja Internet Cafe website as a medium for delivering sales information is the solution. The method that I use is a method of data collection namely observation and literature study and a qualitative approach. The results of this study are that the presence of a viewboard on the Raharja Internet Cafe website can facilitate the admin or guard of Raharja Internet Cafe to make a report to the Raharja University.